Mosaicism in tuberous sclerosis complex: Lowering the threshold for clinical reporting. Issue 12 (6th September 2022) - Ye, Zimeng; Lin, Sufang; Zhao, Xia; Bennett, Mark F.; Brown, Natasha J.; Wallis, Mathew; Gao, Xinyi; Sun, Li; Wu, Jiarui; Vedururu, Ravikiran; Witkowski, Tom; Gardiner, Fiona; et al.
Abstract: Tuberous sclerosis complex (TSC) is a multi‐system genetic disorder. Most patients have germline mutations in TSC1 or TSC2 but, 10%–15% patients do not have TSC1 / TSC2 mutations detected on routine clinical genetic testing. We investigated the contribution of low‐level mosaic TSC1 / TSC2 mutations in unsolved sporadic patients and families with TSC. Thirty‐one sporadic TSC patients negative on routine testing and eight families with suspected parental mosaicism were sequenced using deep panel sequencing followed by droplet digital polymerase chain reaction. Pathogenic variants were found in 22/31 (71%) unsolved sporadic patients, 16 were mosaic (median variant allele fraction [VAF] 6.8% in blood) and 6 had missed germline mutations. Parental mosaicism was detected in 5/8 families (median VAF 1% in blood). Clinical testing laboratories typically only report pathogenic variants with allele fractions above 10%. Our findings highlight the critical need to change laboratory practice by implementing higher sensitivity assays to improve diagnostic yield, inform patient management and guide reproductive counseling.